2020
DOI: 10.1186/s12889-020-08651-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an HIV self-testing intervention: a formative qualitative study among individuals, community leaders, and HIV testing experts in northern Tanzania

Abstract: Background: Achieving the 95-95-95 global targets by 2030, innovative HIV testing models, such as HIV self-testing are needed for people, who are unaware of their HIV status. We aimed to explore key informants, mountain climbing porters, and female bar workers' attitudes, perceived norms, and personal agency related to HIV self-testing. Methods:This was a formative qualitative study to inform the design of an HIV self-testing intervention in Northern Tanzania. Informed by the Integrated Behaviour Model, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 55 publications
(66 reference statements)
5
21
0
Order By: Relevance
“…Although the advantages of using the HIVST kit were greater, most participants noted that they will rather pay less to test for HIV at a health facility. Several participants also reported that their negative past experiences while testing with a healthcare worker at the facility influenced their preferences for HIV selftesting, which was observed in other studies conducted in SSA [33][34][35][36].…”
Section: Discussionsupporting
confidence: 56%
“…Although the advantages of using the HIVST kit were greater, most participants noted that they will rather pay less to test for HIV at a health facility. Several participants also reported that their negative past experiences while testing with a healthcare worker at the facility influenced their preferences for HIV selftesting, which was observed in other studies conducted in SSA [33][34][35][36].…”
Section: Discussionsupporting
confidence: 56%
“…In South Africa, researchers found that participants had a high average usability index of 93.8% for HIVST (44). In Tanzania, participants reported positive attitudes toward HIVST, supportive perceived norms, and self-efficacy (51). In Malawi and Zambia, most women and male partners thought home-based testing and secondary distribution of HIV self-test kits were acceptable (36).…”
Section: Kenya Women Cohort Study 280 Participantsmentioning
confidence: 99%
“…This helps ensure that all the people who were given kits use them to test themselves and get to know their status. Participants from a study conducted in Tanzania [ 33 ] also mentioned the need to follow people who are given kits as failure to do so may lead to delayed initiation into care among HIV-positive participants.…”
Section: Discussionmentioning
confidence: 99%